Severe ischemia dueto intra,arterial injection of molar solution of sodium bicarbonate. - Rudnitzky, Omar; Sciuto, Fernando; Blanco, Raúl; Sueta, Patricia; Blanco, Adriana; Mazza, Milton (Cirugía del Uruguay, 1987)
The authors present three cases of severe acute lower limb isc;hemia alter inadvertent administralion <>f molar solution ol sodium blcarbor111te durlng reanimation alter cardiac arrest, The clinlcal aspects, therapeutic¡¡ I management and results obtained are disc;ussed. Emphasis is set on the lact that no other cases like these